Pengaruh Arus Kas Operasi, Arus Kas Investasi, Arus Kas Pendanaan Dan Laba Akuntansi Terhadap Return Saham (Studi Kasus Pada Perusahaan Manufaktur Sektor Industri Barang Konsumsi Sub Sektor Makanan Dan Minuman Periode 2015-2019) - Yusnita, Irni (CV. ITTC INDONESIA, 2022)
This Study aims to test partially and simultaneously the effect of operating cash flow, investments cash flow, financing cash flow, and accounting profit on stock returns in the food and beverage sub-sector consumer goods industry companies 2015-2019. The type of data used in this research is secondary data. The sampling technique in this research is purposive sampling.while the data analysis used is descriptive statistics and multiple regression with the help of the SPSS 16 for windows program.Based on the results of this study, it can be concluded that operating cash flow and investment cash flow have no effect on stock returns which are partially tested (t test). Funding cash flow and accounting profit affect stock returns which are partially tested (t test). While the simultaneous testing (jointly) concludes that there is a joint (simultaneous) influence between operating cash flow, investment cash flow, financing cash flow and accounting profit on stock returns. Test of the coefficient of determination (adjusted r square) of 0,309, it means that 30,9 % of the independent variables consist of operating cash flow, investment cash flow, financing cash flow and accounting profit to the dependent variable, namely stock returns. While 69,10 % is influenced by other variables which are not included in this study.